THE DYNAMICS IN THE RECOGNITION OF CUSTOMARY JUSTICE IN THE POLITICS OF LAW OF THE JUDICIARY IN INDONESIA - I Ketut Sudantra (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis study aims at discussing the dynamics of the legal recognition of customary justice in politics of law of the judicial power in Indonesia. In accordance with the nature of the analysis, namely, the normative legal analysis, the approach used in this study is the statute approach completed with historical and futuristic approach of the law. The study results show that the recognition of customary justice in the politics of law in Indonesia has been dynamic along with the change of government. In the colonial time of the Dutch East IndiesÂ government, there were two forms of customary justice formally recognized, namely, the indigenous justice ( inheemsche rechtspraak ) and the village justice ( dorpjustitie ).These conditions remained prevailing at the time of the Japanese occupation and in the early days of Indonesian independence. In 1951, the existence of customary courts were abolished gradually and brought an end in 1970 in which the existence of the formal justice system of out-of-the state court- settlement was not allowed anymore. The customary courts abolished in 1951 were indigenous justice (inheemsche rechtspraak) while the existence of village justice (dorpjustitie) continued to berecognized. In theÂ Judicial Power Act of 2009 applied at present, there is no provision which gives recognition of customary justice, but in the laws governing special autonomy for Papua Province - a province in eastern Indonesia â€“ the existence of customary court is explicitly recognized . From the program of national legislation in the House of Representatives of the Republic of Indonesia, it is known that in the future it seems customary justice will be recognized nationally by legislation governing the unity of customary law societyKeywords: customary justice, the unity of customary law society, politics of law.